Stereospecific synthesis of C-arabinofuranosides and carba-disaccharide analogues of Motif C of cell wall AG complex of Mtb - Patil, Rahul S.; Ahire, Ketan M.; Ramana, C. V. (Tetrahedron Letters, 2012)
A simple strategy for the synthesis of alpha- and beta-C-arabinofuranosides featuring a furan ring transposition reaction has been developed. A novel double furan ring transposition reaction has proposed and executed for the synthesis of the carba-disaccharide analogue of Motif C of the cell wall AG complex of Mtb. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Arabinose; C-Glycosides; Carba-disaccharide; Cell wall AG complex; Ring transposition